Discursive practices and creation of identity using the mobile phone - Lloyd, Clare; Gillard, P. (IGI Global, 2010)
This chapter investigates the use of mobile phones in Australia by 18 to 35 year olds in the Hunter region; more particularly how the social construction of mobile phone use is revealed in discourse and related to identity formation. Interviews, collected cultural artifacts and a Research Journal provided the primary material, and the method of Discourse Analysis was used to consider each source of information and to compare them. Choices of phone, wallpaper and ringtone are consciously used to express aspects of individual identity, adapting functions of the mobile phone and engaging with broader discourses such as fashion and sound. Many of these discursive practices with the mobile phone are adopted for pleasure as well as utility.